Learning styles and formative assessment: Study with Chilean Physical Education university students - Serra-Olivares, J.; García-Rubio, J.; Gil Madrona, P.; Cejudo Armero, C.; González Víllora, S. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
Assessment contributes to students learning. Formative assessment is a useful strategy of the initial teacher training. Perceptions about the assessment of Chilean university Physical Education students (n = 95), depending on their learning style, gender and academic course were analyzed. The Learning Styles Questionnaire and the Spanish version of the Assessment Experience Questionnaire were used. The results showed negative perceptions about the assessment process. Significant differences were observed in the perceptions about the use of feedback depending on the learning style of the students (F = 1.062, p =. 004). Significant differences were observed in the perception about the amount of effort (F = 5.888, p =. 000), the suitability of the evaluation (F = 3.282, p =. 015) and the shallow approach to the learning (F = 5.472, p =. 001), depending on the academic course. Gender was not a determinant of perceptions. The findings suggest the use of traditional procedures of assessment (summative assessment) with the students. On the other hand, findings show the influence of learning stylesand the academic course on student perceptionsand learning styles and feedback. This information contributes to a deeper understanding of the learning mode of the students according to their characteristics and context.